Simulation of Human Gentamicin Pharmacokinetics in an Experimental Enterococcus faecalis Endocarditis Model - Dubé, Laurent (American Society for Microbiology, 2003)
Significant differences between animal and human pharmacokinetics may be responsible for the conflicting results of experimental studies. This study determined the impact of human pharmacokinetic simulation (HPS) on gentamicin activity in an Enterococcus faecalis endocarditis model. The decrease in bacterial counts was greater with HPS than with a dose-equivalent regimen without HPS.